The Influence of Digital Financial Literacy on Digital Payment Adoption and Its Impact on the Financial Performance of MSMEs - Sari, Pipit Buana; Sari , Maya Macia (Universitas Dehasen Bengkulu, 2025)
This study examines the influence of digital financial literacy on the adoption of digital payment systems and its subsequent impact on the financial performance of Micro, Small, and Medium Enterprises (MSMEs). Using a quantitative explanatory approach, data were collected from MSME owners through structured questionnaires and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results show that digital financial literacy significantly enhances the adoption of digital payment platforms such as e-wallets, QRIS, and mobile banking. The adoption of digital payments is also found to directly improve financial performance by increasing transaction efficiency, strengthening cash flow stability, and supporting more accurate financial record-keeping. Furthermore, digital payment adoption serves as a mediating variable that strengthens the relationship between digital financial literacy and MSME financial performance. These findings highlight the critical role of digital financial capabilities and technological adoption in supporting MSME competitiveness amidst rapid digital transformation. The study contributes to the existing literature by providing empirical evidence on the mechanisms through which digital literacy and payment technologies shape financial outcomes in the MSME sector.